2017
DOI: 10.1002/2017ja024283
|View full text |Cite
|
Sign up to set email alerts
|

Variabilities of Low‐Latitude Migrating and Nonmigrating Tides in GPS‐TEC and TIMED‐SABER Temperature During the Sudden Stratospheric Warming Event of 2013

Abstract: The Global Positioning System deduced total electron content (TEC) data at 15°N (geomagnetic), which is the crest region of equatorial ionization anomaly, are used to study tidal variabilities during the 2013 sudden stratospheric warming (SSW) event. The results from space‐time spectral analysis reveal that the amplitudes of migrating diurnal (DW1) and semidiurnal (SW2) tides are larger than those of nonmigrating tides. After the SSW onset, the amplitudes of DW1, SW2, SW1, and DS0 increase. Moreover, they show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…For this purpose GPS TEC data are utilized. The tidal components are derived as described in Sridharan (, ). Figure a shows the daily variation of amplitudes of PW of k = 1 and k = 2 in temperature at 60°N and 10 hPa for the period 1–120 days starting from 1 December 2008.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose GPS TEC data are utilized. The tidal components are derived as described in Sridharan (, ). Figure a shows the daily variation of amplitudes of PW of k = 1 and k = 2 in temperature at 60°N and 10 hPa for the period 1–120 days starting from 1 December 2008.…”
Section: Resultsmentioning
confidence: 99%
“…First, the time variation of TEC at each longitude is subjected to Fourier transform TEC(),λt=tCt()tCos()ωt+St()tSin()ωt to obtain time variation of Fourier coefficients C t ( t ) and S t ( t ) for each frequency “ ω ”. These time variations of Fourier coefficients for each frequency “ ω ” are subjected to Fourier transform in longitude to get Fourier coefficients corresponding to different zonal wave numbers (Sridharan, , ). From these coefficients, the amplitudes and phases are calculated.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that 16‐day oscillations are more prominent in the observations during boreal winter and are especially evident in proximity to SSW events, including observations of 16‐day oscillations in TEC (Sridharan, ), ionosonde data (Gupta & Upadhayaya, ), and in ionospheric currents (Vineeth et al, ). Sassi et al () have shown that the intrinsic frequency of a Rossby 16‐day wave is quite different before and after an SSW, illustrating that the background winds can change the propagation characteristics of these modes in the upper atmosphere.…”
Section: Intraseasonal Variabilitymentioning
confidence: 91%
“…Sassi et al () have shown that the intrinsic frequency of a Rossby 16‐day wave is quite different before and after an SSW, illustrating that the background winds can change the propagation characteristics of these modes in the upper atmosphere. Sridharan () used GPS TEC maps and temperatures from SABER on board the Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED) satellite to study tidal variability during the 2013 SSW event; they found that after the onset of the SSW, the amplitudes of the migrating diurnal (DW1) and semidiurnal (SW2) tides at zonal wavenumbers 1 and 2, respectively, as well as nonmigrating tides (such as the semidiurnal westward propagating at zonal wavenumber 1, or SW1, and the diurnal zonal mean oscillation, or D0) generated by nonlinear interactions with PWs increased and exhibited a 16‐day periodicity. Gupta and Upadhayaya () also found quasi‐16‐day periodicities in ionosonde F 2 layer critical frequency ( f o F 2 ) during SSWs.…”
Section: Intraseasonal Variabilitymentioning
confidence: 99%
“…However, the ionospheric day‐to‐day variability could still be influenced by nonlinear interaction of planetary waves and widely existed tides. Many studies have clearly identified ionospheric variations such as large perturbations of ion temperature (e.g., Goncharenko & Zhang, ), peak electron density ( f o F 2 ; e.g., Yue et al, ; Pancheva & Mukhtarov, ; Gupta & Upadhayaya, ), total electron content (e.g., Chau et al, ; Goncharenko et al, ; Goncharenko et al, ; Sridharan, ), equatorial electric field (e.g., Fejer et al, ), and equatorial electrojet (e.g., Sridharan et al, ) during SSW periods.…”
Section: Introductionmentioning
confidence: 99%